Analisa Risiko Keselamatan Dan Kesehatan Kerja (K3) Pada Kegiatan Docking Di PT. Pelindo Marine Service - Muhammad Luqman Dzaky; Naniek Ratni JAR (Jurnal Universal Technic, 2024)
The importance of K3 aspects in docking activities not only includes individual safety, but also has a direct impact on productivity and operational continuity. Accidents or incidents that occur during the docking process can not only threaten the lives and health of workers, but can also cause detrimental environmental impacts and hinder the smooth running of the supply chain. The HIRARC method allows identifying various potential hazards that may be associated with an activity or work environment. This approach involves data collection, situational analysis, and determining appropriate mitigation measures. From the results of the identification carried out during ship docking activities at PT. Pelindo Marine Service has 14 activities that have potential danger. With 4 activities that have very low risk, namely maintenance and repair activities in the engine room, ship maintenance in closed rooms, maintenance and repairs in the electrical room, and manual lifting of heavy materials. Then there are 5 activities with low risk, including welding process activities in open spaces, carrying out repair work at height, operating cranes, cleaning ship rooms, and plate cutting (LPG gas cutting) and material grinding processes. 3 activities with medium/medium risk, namely working around waters, working/standing around ships, and stuffing/stripping activities. And there is 1 activity with high risk, namely the ship maintenance process using the welding process in a closed space and 1 activity with very high risk, namely the activity of filling gas cylinders (for cutting and welding equipment). The risks faced include slipping, falling, scratches, shortness of breath, weakness, eye irritation, injuries, minor injuries, serious injuries, sprains, burns, fractures, electrocution and others. And the efforts made to control the risks above include using Personal Protective Equipment with discipline, working according to SOPs, installing K3 signs, providing fire extinguishers, regular inspections and implementing a good ventilation system. Based on the results of risk identification in ship docking activities at PT. Pelindo Marine Services. The importance of effective and continuous implementation of K3 in ship docking activities, in order to maintain the safety, health and welfare of workers and minimize negative impacts on company operations